Modern Methods Applied in Teaching Physics - Miroslav Nemec (Communications - Scientific letters of the University of Zilina, 2010)
This paper deals with modernization of teaching acoustics. We prepared the study material with qualitative exercises. In the text we pay attention to physical and ecological aspects of sound and noise. Further we analyze sound as an example of mechanical waves. The main part of the work is creation of video experiments in the field of acoustics as well as experiments supported by the computer software that would enable analysis of sounds and sound filters. We created ten experiments and further developed them into methodological and study material.